Association of right precuneus compression with apathy in idiopathic normal pressure hydrocephalus: a pilot study - Yoshihiro Chadani; Tetsuo Kashibayashi; Takahiro Yamamoto; Atsushi Tsuda; Ryoko Fujito; Masanori Akamatsu; Naoto Kamimura; Ryuichi Takahashi; Takuji Yamagami; Hirokazu Furuya; Tetsuya Ueba; Motoaki Saito; et al. (Scientific Reports, 2022)
Abstract Apathy is frequently observed in idiopathic normal pressure hydrocephalus (iNPH) and worsens cognitive impairment and gait disturbance. In this study, we evaluated the regions associated with apathy in iNPH using statistical imaging analysis on the whole brain, both in terms of cerebral blood flow and gray matter volume. Twenty-seven patients with iNPH were assigned to two groups based on their scores on the neuropsychiatric inventory items related to apathy; 18 patients were assigned to the group with apathy (iNPH + APA) and 9 to the group without apathy (iNPH − APA). The magnetic resonance images and cerebral blood flow single-photon emission computed tomography data of the two groups were compared using statistical parametric mapping 12. The regional gray matter volume of the right precuneus was significantly larger in the iNPH + APA group than in the iNPH − APA group, but the regional cerebral blood flow in any region of the brain was not significantly different between the two groups. These results suggested that the larger gray matter volume, which is thought to reflect gray matter compression, in the precuneus might be involved in apathy in iNPH.